Death from COVID-19 in contexts of social deprivation in Mexico - Martínez-Martínez, Oscar A.; Ramírez-López, Araceli; Coutiñho, Brenda; Reyes-Martínez, Javier (Frontiers in Public Health, 2024)
Poverty is one of the macro factors that has been little studied in terms of its effect on death from COVID-19 since most studies have focused only on investigating whether the pandemic increased poverty or not. With that on mind, the present study aims to analyze how the social deprivations that comprise the measurement of municipal poverty in interaction with health comorbidities and sociodemographic characteristics, increased the probability of death from COVID-19. The study is cross-sectional and covers daily reports on the conditions of COVID-19 in the Mexican population for almost two years. Using data from the National Epidemiological Surveillance System and the National Council for Evaluation of the Social Development Policy (N= 5,387,981), we employ a Generalized Linear Mixed Model (GLMM), specifically a binomial generalized linear mixed model. Results indicate that, besides comorbidities, sociodemographic traits, and clinical aspects, living in a municipality where one or more of the social deprivations exist increases the probability of death. Specifically, in those municipalities where there is deprivation in education, social security, and food, as well as deprivation due to access to health services and deprivation in household services, the probability of death was greater. Thus, it can be concluded that living in a municipality with one or more of the social deprivations that compose poverty generated a greater probability of death. Each one of them or together, shows that poverty is a substantial factor for a pandemic like COVID-19 to worsen contagion and death, becoming a circle from which it is difficult to escape.